Towards Understanding the Relationship Between Personality Types and Homeopathic Remedies in an Integrative Health Approach - Esra Tosun; Ali Timucin Atayoglu (Journal of Mind and Medical Sciences)
Objective: This study aims to explore the integration of Enneagram personality types with homeopathic prescribing by evaluating the relationship between personality traits and the corresponding homeopathic remedies, enhancing individualized care through an analysis of the possible mind rubrics. Method: Personality traits from the dynamic Enneagram model were mapped to corresponding mental–emotional traits. These traits were matched to the relevant possible rubrics in the Synthesis Treasure Edition repertory, using Radar Opus software. A total of 36 analyses were conducted across nine personality types. The frequency distribution (%) of remedies appearing in the top five rankings was analyzed, identifying remedies corresponding to the highest number of rubrics. Results: Forty rubrics were used in the repertorization, with duplicate rubrics counted only once, and nine different remedies were identified with a value of four points. The frequency distribution showed that polychrest remedies appeared most frequently in the top five rankings across all 36 analyses, indicating a relationship between certain remedies and personality traits. Conclusions: Integrating Enneagram personality traits into homeopathic prescribing could enhance individualized care by providing additional insights for remedy selection, alongside the traditional approaches that are commonly used, such as case analysis using the totality of symptoms. Further research is needed to refine and validate this approach.